Optimasi Proses Pengeringan Tepung Jamur Tiram Putih (Pleurotus ostreatus) - Netty Widyastuti; Sri Istini (Fakultas Farmasi Universitas Pancasila, 2004)
This study deals with the determination of the nutritional content of oyster mushroom (Pleurotus ostreatus). An attempt is made to attain better physical properties of the powder after drying. The first procedure consists of drying of ground fresh oyster mushroom at 50°C and 60° C during 24, 48 and 72 hours, while according to the second procedure slices of fresh oyster mushroom are first dried at 40°C (during 24 and 48 hours), than powdered. Laboratory analysis shows that the content (% w/w) of fresh mushroom is as follows: fiber 3.44, fat 0.10, protein 3.15, carbohydrate 0.63 and glutamic acid 0.94. The result of the first procedure is a sticky and brownish powder, while that of the second attempt (dried at 40°C during 24 hours) is a white and fine powder, which can be directly capsuled.